Identifying Naturalistic Coaching Behavior Among Practicing Surgeons in the Operating Room. Issue 1 (January 2021) - Pradarelli, Jason C.; Delisle, Megan; Briggs, Alexandra; Smink, Douglas S.; Yule, Steven
Abstract : Objective: The aim of this study was to identify examples of naturalistic coaching behavior among practicing surgeons operating together by analyzing their intraoperative discussion. Background: Opportunities to improve surgical performance are limited for practicing surgeons; surgical coaching is one strategy to address this need. To develop peer coaching programs that integrate with surgical culture, a better understanding is needed of how surgeons routinely discuss operative performance. Methods: As part of a "co-surgery" quality improvement program, 20 faculty surgeons were randomized into 10 dyads who performed an operation together. Discourse analysis was conducted on transcribed intraoperative discussions. Themes were coded using an existing framework of surgical coaching principles (self-identified goals, collaborative analysis, constructive feedback, peer learning support) and surgical coaching content (technical skills, nontechnical skills). Coaching principles were cross-referenced with coaching content; c-coefficient measured the strength of association between pairs of themes. Results: Overall, 44 unique coaching examples were identified in 10 operations. Of the 4 principles of surgical coaching, only self-identified goals and collaborative analysis were identified consistently. Self-identified goals were most associated with discussions regarding technical skills of "tissue exposure, " "flow of operation, " and "instrument handling" and the nontechnical skill "situation awareness." Collaborative analysis was most associated with discussions regarding technical skills of "respect for tissue" and "flow of operation" and nontechnical skills of "communication and teamwork." Conclusions: In naturalistic discussions between practicing surgeons in the operating room, numerous examples of unprompted coaching behavior were identified that target intraoperative performance. Prominent coaching gaps—constructive feedback and peer learning support—were also observed. Surgical coach trainings should address these gaps.